ANALISIS SEGI BANGUN DATAR DALAM PERMAINAN LOMPAT TIUNG DI DESA MUBUNG KABUPATEN KAPUAS HULU - Desiana, Wahdah; Aminah, Aminah (IAIN Pontianak, 2023)
The purpose of this study was to describe the ethnomathematics of Jump Tiung (a traditional game located in Mubung Village, Hulu Hurung District, Kapuas Hulu District). This research was also to make teaching materials in the form of student worksheets. This type of research is qualitative research with an ethnographic approach. Data collection methods used are observation, interviews, and documentation. The object of this study was Tiung Jump (traditional game) with a speaker by Wahdah Desiana in Mubung Village, Hulu Gurung District, Kapuas Hulu District. Based on the results of this study it can be seen that Jump Tiung (traditional game) has a mathematical element. The mathematical elements found are plane shapes, nets, congruence, congruence, and reflection.